The characteristic of the engine qualities of the students of technical institute of III functional health group (special medical group) - L.N. Prosvirina; M.M. Kolokoltsev; M.A. Kolchanova; Miroslawa Cieslicka; Blazej Stankiewicz (Physical Education of Students)
Purpose : the study of the dynamics of engine qualities in the students of III functional health group (special medical group) dependent on age taking into account the frequency of occupations by physical culture for the correction of the program of their physical training. Material: the physical condition is evaluated among 467 students at the age from 18 to 21 year. Observation is carried out in the dynamics of the instruction of students at the university from 1 through 5 semesters. Results: installed age characteristics of physical readiness of students, depending on the frequency of physical training. It is shown that the passage to the single-time in the week occupations by physical culture reliably decreases their physical condition. The features of the dynamics of the physical fitness of students. Conclusions : monitoring the physical fitness of students can be considered as a factor in strengthening the pedagogical orientation of physical education of youth. Should pay particular attention to the development of motor abilities missing with appropriate exercise. Students are encouraged to use the self-study managed to maintain the required physical condition, as well as the mandatory maintenance of a diary of self-control.